Urna electrónica para votaciones en la Universidad Técnica Estatal de Quevedo - Cadena Toala , Marvin Joel (2024)
This research project aims to develop an electronic voting booth for in-person remote voting at the Technical State University of Quevedo (UTEQ) in Ecuador. The initiative stems from the need to enhance electoral processes within the institution, which face challenges related to transparency, efficiency, and participation. To address these issues, the proposal involves the use of innovative technology that will simplify the voting process, enhance accuracy in vote collection and counting, and contribute to the integrity of the electoral process